Nurses' perceptions of barriers and facilitators and their associations with the quality of end‐of‐life care. Issue 3 (20th December 2017) - Omar Daw Hussin, Emni; Wong, Li Ping; Chong, Mei Chan; Subramanian, Pathmawathi
Abstract : Aims and objectives: To examine nurses' perceptions of barriers to and facilitators of end‐of‐life care, as well as their association with the quality of end‐of‐life care. Background: Often, dying patients and their families receive their care from general nurses. The quality of end‐of‐life care in hospital wards is inadequate. Method: A self‐administered questionnaire was completed by 553 nurses working in a tertiary teaching hospital in Malaysia. Results: The barrier with the highest mean score was "dealing with distressed family members." The facilitator with the highest mean score was "providing a peaceful and dignified bedside scene for the family once the patient has died." With regard to barrier and facilitator categories, the barrier category with the highest total mean score was patient‐related barriers and the facilitator category with the highest total mean score concerned facilitators related to healthcare professionals. In the multivariate analysis, age, patient family‐related barriers and healthcare professional‐related facilitators significantly predict the quality of end‐of‐life care. Conclusion: The results of this study suggest that there is an urgent need to overcome barriers related to the patient and family members that hinder the quality of care provided for dying patients, as well as to enhance and implement the facilitators related to healthcare providers. In addition, there is also a need to enhance the quality of end‐of‐life care provided by younger nurses through end‐of‐life care courses and training. Relevance to clinical practice: Helping nurses overcome barriers and implement facilitators may lead to enhanced quality of care provided for dying patients.